2010
DOI: 10.11646/zootaxa.2501.1.2
|View full text |Cite
|
Sign up to set email alerts
|

New species of reed frog from the Congo basin with discussion of paraphyly in Cinnamon-belly reed frogs

Abstract: We describe a new species of Afrotropical reed frog, genus Hyperolius (Hyperoliidae), from Salonga National Park in the central Congo basin, Democratic Republic of Congo. Males and females have similar colour and pattern and are easily distinguished from other taxa by a relatively short and broad, bright yellow (in life), dorsolateral line ending in the sacral region and the presence of a light spot on the heel. In a 16S mitochondrial rRNA phylogeny, it clusters with samples allocable to the Cinnamon-belly ree… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 17 publications
1
11
0
Order By: Relevance
“…The Hyperolius cinnamomeoventris species complex is distributed in disturbed forest, moist savanna and bushland habitats across Central Africa and is hypothesized to consist of several cryptic species (Lötters et al ., ; Schick et al ., ). We recovered substantial genetic diversity across the species range, consistent with a previous mitochondrial study that identified four regional clades in the H. cinnamomeoventris species complex, including H. veithi , a newly described species from the central Congo basin (Schick et al ., ). We identified three distinct clades (not including H. veithi ) across the Central African range of H. cinnamomeoventris that correspond to West‐Central, North/East‐Central and South‐Central Africa (clades A through C, respectively).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…The Hyperolius cinnamomeoventris species complex is distributed in disturbed forest, moist savanna and bushland habitats across Central Africa and is hypothesized to consist of several cryptic species (Lötters et al ., ; Schick et al ., ). We recovered substantial genetic diversity across the species range, consistent with a previous mitochondrial study that identified four regional clades in the H. cinnamomeoventris species complex, including H. veithi , a newly described species from the central Congo basin (Schick et al ., ). We identified three distinct clades (not including H. veithi ) across the Central African range of H. cinnamomeoventris that correspond to West‐Central, North/East‐Central and South‐Central Africa (clades A through C, respectively).…”
Section: Discussionmentioning
confidence: 97%
“…The gene trees reveal that the island endemic Hyperolius form a clade that renders H. cinnamomeoventris paraphyletic, consistent with a previous mitochondrial phylogenetic study (Schick et al ., ). This result confirms that a clade within the H. cinnamomeoventris species complex is the sister taxon to the island endemics and indicates that island endemics probably resulted from one colonization from the mainland and subsequent diversification within the Gulf of Guinea.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…We included 254 hyperoliid samples in our sequence capture experiment with multiple representatives per species when possible. Although there are 230 currently recognized hyperoliid species (AmphibiaWeb, 2018), this family is in a state of taxonomic flux with recent studies recommending both the synonymy of species names and the splitting of species complexes (Rödel et al 2002; Rödel et al 2003; Wollenberg et al 2007; Rödel et al 2009; Rödel et al 2010; Schick et al 2010; Conradie et al 2012; Dehling 2012; Channing et al 2013; Conradie et al 2013; Greenbaum et al 2013; Liedtke et al 2014; Loader et al 2015; Portik et al 2016a; Bell et al 2017a; Conradie et al 2018). We estimate that our sampling represents approximately 143 distinct hyperoliid lineages including 12 of 17 described hyperoliid genera.…”
Section: Methodsmentioning
confidence: 99%
“…The material obtained from these trips was important for a number of taxonomic revisions. The Angolan river frog Amietia angolensis, previously thought to be widespread in Africa, was found to occur only in Angola (Channing and Baptista 2013;Channing et al 2016), reed frogs of the Hyperolius nasutus complex (Channing et al 2013) were shown to include numerous cryptic species, with possibly four occurring in Angola, and the Hyperolius cinnamomeoventris complex was split into different sister clades (Schick et al 2010).…”
Section: Recent History and Increase Of Informationmentioning
confidence: 99%